2021
DOI: 10.1098/rsos.210518
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals multiple origins and migration waves of extinct Japanese brown bear lineages

Abstract: Little is known about how mammalian biogeography on islands was affected by sea-level fluctuations. In the Japanese Archipelago, brown bears ( Ursus arctos ) currently inhabit only Hokkaido, the northern island, but Pleistocene fossils indicate a past distribution throughout Honshu, Japan's largest island. However, the difficulty of recovering ancient DNA from fossils in temperate East Asia has limited our understanding of their evolutionary history. Here, we analysed mitochondrial DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
0
15
5
Order By: Relevance
“…This suggests population continuity in these regions over at least the last 11,000 to 50,000 years. Population continuity in North America and Japan is in contrast with previous hypotheses of multiple migration events based on mitochondrial genomes [9,11]. However, as we uncovered large after the end of the Pleistocene, and before the mid-Holocene.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This suggests population continuity in these regions over at least the last 11,000 to 50,000 years. Population continuity in North America and Japan is in contrast with previous hypotheses of multiple migration events based on mitochondrial genomes [9,11]. However, as we uncovered large after the end of the Pleistocene, and before the mid-Holocene.…”
Section: Discussioncontrasting
confidence: 99%
“…In contemporary North American brown bears, three genetically divergent mitochondrial lineages have been described, leading to the hypothesis of three independent colonisation events from Eurasia [9]. In addition, independent colonisation events have also been hypothesised for Asia; timing of divergence estimated from mitochondrial genomes retrieved from Japanese brown bears have led to suggestions that brown bears migrated from mainland Eurasia to Japan at least twice [11]. However, the mitochondrial genome represents just a single loci, is exclusively maternally inherited, and may be heavily confounded by gene flow and incomplete lineage sorting [12,13], which can lead to erroneous inferences.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate picture of the historical relationships among contemporary populations is the foundation for all evolutionary inference. Due to climatic oscillations, multiple waves of colonization and admixture are common in the wild (Hudson et al, 2021 ; Marques, Lucek, et al, 2019 ; Schenekar et al, 2014 ; Segawa et al, 2021 ; Shirsekar et al, 2021 ) and many analytical methods can be seriously misled unless the resulting population structure and demographic history are correctly accounted for (Gompert & Buerkle, 2016 ; Lange, 2021 ; Scerri et al, 2018 ; Theunert & Slatkin, 2017 ; Vitti et al, 2013 ). The results of the current study provide a case in point: our analyses uncovered an unexpectedly complicated history of northern European sticklebacks pointing to multiple historical invasions and admixture events.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the above-mentioned possibility that wolf populations expanded into the Japanese archipelago several times, it was recently reported that the now-extinct Honshu brown bear also came into existence on Honshu via multiple migrations of ancient lineages from Eurasia to Honshu. 43 Thus, the mammalian fauna of the Japanese archipelago may have ''multi-layered'' histories of migrations as a consequence of the land connections that formed intermittently between the Japanese islands and Eurasia during the Pleistocene, and this is one of the most important topics of ongoing research with ancient DNA.…”
Section: Discussionmentioning
confidence: 99%